Effects of machining method and technique on galvanized steel material properties - Abdul Rani, Nadia; Abdul Aziz, Faieza; Hemdi, Abdul Rahman; Kanagaraj, Mohanadhas (IOS Press, 2021)
Machining or metal cutting operation is the process of removing unwanted material in the form of chips, from a block of metal, using cutting tool is the most widely used industrial practice for which sustainable manufacturing is an appropriate approach. Aligning with rapidly changing scenario in manufacturing industries, applications of optimization techniques in metal cutting processes is essential for a manufacturing unit to respond effectively to severe competitiveness and increasing demand of quality product in the market. When machining structural parts with high material removal rates, the stiffness of the machine tool can be one of the limited factors due to the machining vibrations or called chatter vibrations. Computer Numerical Controller (CNC) machining is one of the machining method used to get a high accuracy results in product and Wire Electrical Discharge Machining (WEDM) is one of the advanced technique primarily used for hard metals or those that would be very difficult to machine with traditional techniques, such as conventional milling operation. Due to this non-contact operation towards the work piece, it shallower the heat-affected zone (HAZ) which may effect on the material properties. In this paper, galvanized steel has been used to identify the changes in its mechanical properties by using tensile test with both machining methods and techniques to produce the T-bone specimen. Hence the static or tensile properties of the specimen is obtained, a good machining procedure could be determined. Therefore, it will decrease the strength of material and increase the durability and reliability of product.